Intertextuality in Avatar : the last airbender / Tan Renjie - Tan, Renjie (2014)
The purpose of this dissertation is to study the intertextual references drawn from cultures and practices in our world that are incorporated into the formation of the fictional world of the Nickelodeon animation Avatar: The Last Airbender. This animation that was created and produced by Michael Dante DiMartino and Bryan Konietzko for Nickelodeon has enjoyed and garnered much success worldwide. This qualitative research uses the conceptual framework of intertextuality to code the data gathered from the animation into a manner that best illustrates the animation’s intertextual references that are drawn from the cultures in our world. The research design was specifically created by the researcher to analyze references of landscapes and architecture, clothing and lifestyles in the animation in terms of their visual and verbal references. The results show that these references were drawn from the Inuit, Native American, Chinese, Japanese, Tibetan and Bhutanese cultures. This study would reveal how these numerous references are realized and exhibited in the animation as well as increase the limited literature that has been conducted upon this genre. Keywords: Intertextuality, Animation, Avatar: The Last Airbender